Cordierite material prepared from magnesium waste porcelain and preparation method of cordierite material
By using magnesium waste porcelain and specific raw materials in cordierite heat-resistant porcelain materials, the firing temperature is reduced and the magnesium-rich silicon glass phase is introduced, the problems of high firing temperature and insufficient performance of traditional cordierite materials are solved, and the problem of high firing temperature and insufficient performance is achieved. The preparation of high-strength and low expansion coefficient of ceramics is in line with the concept of green environmental protection.
Patent Information
- Application Number
- CN202411294923.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional cordierite heat-resistant porcelain materials have high firing temperature and high cost, and are difficult to synthesize materials with high crystallinity at lower temperatures, which have problems with harmful heterophasic phases, low strength and low thermal shock resistance.
Magnesium waste porcelain is used as the precursor, and by introducing high-active magnesium-rich silicon glass phase and original pyroxene as cordierite transformation mesophase, the firing temperature is reduced to 959℃, and high-strength and low expansion are generated at 1220-1260℃. The ceramic body with coefficient is prepared using the specific ratio and process of magnesium waste porcelain, talc, clay raw materials and high alumina raw materials.
It realizes the preparation of high-performance heat-resistant porcelain at lower firing temperatures, reduces dependence on scarce resources, reduces energy consumption and carbon emissions, improves the performance and strength of ceramics, and solves the low expansion coefficient and resistance of traditional methods. The problem of low folding strength.
Smart Images

Figure CN119219402A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic materials, and in particular to a cordierite material prepared by utilizing magnesium waste porcelain and a preparation method thereof. Background Art
[0002] Cordierite materials have the characteristics of low thermal expansion coefficient, excellent thermal shock stability and corrosion resistance, and have gradually begun to be used in the heat-resistant porcelain industry in recent years. The traditional formula for preparing low-expansion cordierite materials is mainly kaolin-talc-alumina, or replaced with other similar raw materials. At present, cordierite heat-resistant porcelain still has the following two key problems: First, the firing temperature requires high firing temperature. The firing temperature of the traditional kaolin-talc-alumina formula is generally 1300-1350℃. In order to cater to the green production concept of energy conservation and emission reduction, the firing temperature of daily-use ceramics industry is developing towards medium and low temperatures. However, it is difficult to synthesize cordierite with high crystallinity at a low firing temperature, and there are more harmful impurities in the product, such as (square) quartz, corundum, etc., which leads to the performance of the cordierite heat-resistant porcelain produced being far inferior to that of using lithium ore as the main raw material. This also makes most companies have to use scarce and expensive lithium ore in order to take into account product performance and quality stability. Second, the strength and thermal shock resistance are low. In order to make cordierite heat-resistant porcelain be fired at a lower temperature, the most commonly used method is to add some fluxing (mineralizing) agents, such as Nb 2 O 5 , Y 2 O 3 , Li 2 O, ZnO and BaCO 3 Although methods such as these are beneficial for promoting the formation of cordierite phase under medium and low temperature firing conditions, these methods are costly and it is difficult to obtain a microscopic morphology with uniform particle size distribution, and the strength and thermal shock resistance of the products are poor.
[0003] Existing patent documents disclose the use of waste materials to prepare cordierite materials, such as patent application No. 2022105738223, which uses ferrochrome waste slag to prepare cordierite materials, with a firing temperature of 1250-1300°C and an average thermal expansion coefficient of 2.1×10 -6 ~3.1×10 -6 / ℃, flexural strength of 40-55Mp, requiring mechanically activated ferrochrome waste slag particle size D50 not greater than 1μm, making it a high-energy powder to increase its internal crystal defects and promote internal crystal phase transformation. Patent application No. 2013105784970 discloses a preparation method for synthesizing cordierite material using waste ceramic rollers, the formula includes waste ceramic rollers, kaolin, talc, quartz, titanium dioxide, the cordierite content is 92-97%, the flexural strength is 50-85MPa, the main crystal phase of the ceramic roller is corundum and mullite, and the low impurity content is used to synthesize high-purity cordierite material and reduce the cost of raw materials. The paper published in 2016, "The Effect of Amount of Bauxite in the Preparation of Cordierite Low Expansion Ceramic Materials from Yellow Sand", uses desert yellow sand, magnesite and bauxite as the main raw materials to prepare cordierite low expansion materials. When the amount of bauxite added is 30%, the thermal expansion performance is the best, and its thermal expansion coefficient is 3.61×10 -6 / ℃, the main crystal phase is cordierite, and there is a small amount of magnesia-alumina spinel.
[0004] In the prior art, there is no report on the preparation of a cordierite material with high strength and low expansion coefficient by using magnesium waste porcelain and the preparation method thereof. Summary of the invention
[0005] The first purpose of the present invention is to address the deficiencies in the prior art and provide a cordierite material with high strength and low expansion coefficient prepared from magnesia waste porcelain. The technical method of introducing a synthetic cordierite precursor is adopted, and a high-activity magnesium-rich silica glass phase and proto-enstatite are introduced through magnesia waste porcelain as cordierite transformation intermediate phases, so that the cordierite precipitation temperature is reduced to 959°C at the lowest. A ceramic body with a low expansion coefficient and high strength can be directly generated at a lower firing temperature (1220-1260°C), thereby realizing the controllable preparation of lithium-free high-performance heat-resistant porcelain.
[0006] The second object of the present invention is to provide a method for preparing a cordierite material with high strength and low expansion coefficient by using magnesium waste porcelain to address the deficiencies in the prior art.
[0007] To achieve the above first purpose, the technical solution adopted by the present invention is:
[0008] A cordierite material prepared from waste magnesia porcelain, comprising the following raw materials: waste magnesia porcelain, talc, clay raw materials, high-alumina raw materials, wherein the weight percentage of the waste magnesia porcelain is 20-40%, and the raw materials are mixed to obtain magnesia:alumina (Al 2 O 3 ): Silicon oxide (SiO 2 ) is in a molar ratio of 0.29:(0.30-0.31):(0.76-0.80).
[0009] Furthermore, the talc is burnt talc, the clay raw material is one or more of kaolin, illite, bentonite, and black mud, and the high-alumina raw material is one or more of alumina, aluminum hydroxide, and bauxite.
[0010] Furthermore, the main crystal phases of the magnesium waste porcelain raw material are protoenstatite and magnesium-rich silicate glass phase.
[0011] As an improvement of the cordierite material prepared by using magnesia waste porcelain in the present invention, the mass ratio of the magnesia waste porcelain, talc, clay raw material, and high-alumina raw material is preferably (20-40): (14-26): (22-32): (22-24). More preferably, the talc is calcined talc, the clay raw material is kaolin, and the high-alumina raw material is bauxite.
[0012] Furthermore, in terms of mass percentage, the composition of the magnesium waste porcelain includes: 55-75% SiO 2 、5-9%Al 2 O 3 , 7-30% MgO, 0.01-5.0% CaO, 0.01-3.0% Fe 2 O 3 0.01-2.0% TiO 2 , 0.01-3.0%K 2 O, 0.01-2.0% Na 2 O.
[0013] As an improvement of the cordierite material prepared by using magnesia waste porcelain in the present invention, it is preferred that the D50 of the waste porcelain raw material is 10-15 μm, and the calcined talc, kaolin and bauxite are sieved through a 250-mesh screen before forming.
[0014] To achieve the above second purpose, the technical solution adopted by the present invention is:
[0015] A method for preparing a cordierite material using magnesia waste porcelain comprises the following steps: mixing raw materials, ball milling, screening, granulating, molding, and high-temperature calcining to obtain the cordierite material; the raw materials comprise magnesia waste porcelain, talc, clay raw materials, and high-alumina raw materials, the weight percentage of the magnesia waste porcelain is 20-40%, and the molar ratio of magnesium oxide:aluminum oxide:silicon oxide after the raw materials are mixed is 0.29:(0.30-0.31):(0.76-0.80).
[0016] Furthermore, the talc is burnt talc, the clay raw material is one or more of kaolin, illite, bentonite, and black mud, and the high-alumina raw material is one or more of alumina, aluminum hydroxide, and bauxite.
[0017] Furthermore, the main crystal phases of the magnesium waste porcelain raw material are protoenstatite and magnesium-rich silicate glass phase.
[0018] As an improvement of the method for preparing cordierite material from magnesia waste porcelain of the present invention, the mass ratio of the magnesia waste porcelain, talc, clay raw material, and high-alumina raw material is preferably (20-40): (14-26): (22-32): (22-24). More preferably, the talc is calcined talc, the clay raw material is kaolin, and the high-alumina raw material is bauxite.
[0019] As an improvement of the method for preparing cordierite material by using magnesia waste porcelain of the present invention, it is preferred that the D50 of the waste porcelain raw material is 10-15 μm, and the calcined talc, kaolin and bauxite are sieved through a 250-mesh screen before forming.
[0020] Furthermore, the high temperature calcination refers to calcination at a temperature of 959-1260° C. and keeping the temperature for 10-60 minutes, preferably calcination at a temperature of 1220-1260° C. and keeping the temperature for 30 minutes.
[0021] The advantages of the present invention are:
[0022] 1. The present invention provides a method for preparing high-performance heat-resistant porcelain by recycling magnesium waste porcelain as a precursor for cordierite synthesis, which realizes efficient reuse of resources, greatly reduces dependence on scarce resources, and effectively cuts raw material costs. At the same time, the lower sintering temperature significantly reduces energy consumption and greatly reduces carbon emissions, which perfectly fits the current green and environmentally friendly development concept. And through a unique formula and process design, a ceramic body with excellent thermal shock resistance (no cracking in heat exchange at 20 to 500°C) is successfully prepared at a relatively low firing temperature (1220 to 1260°C). This technological innovation not only significantly improves the performance of ceramics, but also brings new ideas and methods to the field of heat-resistant porcelain manufacturing.
[0023] 2. The high-activity magnesium-rich glass phase and the main crystal phase protoenstatite in magnesium waste porcelain are preferentially utilized as the cordierite intermediate phase, which not only greatly reduces the precipitation temperature of cordierite to 959°C, but also broadens the crystallization temperature range of cordierite. It also greatly promotes the synthesis of cordierite at a relatively low firing temperature (1220-1260°C), improves the purity and yield of cordierite under medium and low temperature firing conditions, and solves the problems of low thermal expansion coefficient and low flexural strength of medium and low temperature cordierite ceramics.
[0024] 3. Utilize the high activity of the magnesium-rich glass phase of magnesium waste porcelain to promote the transformation of harmful impurities such as quartz and corundum into cordierite phase and spinel reinforcement phase, form a dispersed spinel toughened cordierite microstructure, and realize the preparation of high-strength cordierite ceramics at a lower firing temperature (1220-1260°C), solving the problem of the compatibility of low expansion coefficient and high strength of traditional cordierite porcelain at a lower firing temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] AttachedFigure 1 The XRD patterns of different types of ceramic waste materials, including (a) daily waste ceramics, (b) bathroom waste ceramics, and (c) magnesium waste ceramics.
[0026] Attached Figure 2 The DTA curves of Comparative Example 1 and Examples 3 / 6 are shown.
[0027] Attached Figure 3 The XRD patterns of different formulations at different sintering temperatures in the low temperature range are shown in Figure 1. The left figure is the formulation of Comparative Example 1, and the right figure is the formulation of Example 3 / 6.
[0028] Attached Figure 4 The figure below is a comparison of the effect of adding magnesium waste porcelain on the microstructure of cordierite products (SEM-EDS mapping). The left figure is comparative example 1, and the right figure is example 6. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0030] The experimental methods in the following examples without specifying specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. The contents in the following examples are all weight percentages. The chemical composition of the raw materials used in the examples is shown in the following table. The XRD spectrum of the waste porcelain raw material is shown in Figure 1 shown.
[0031] Table 1 Chemical composition of raw materials (wt / %)
[0032]
[0033] Test Method
[0034] The calcined samples of each embodiment and comparative example were tested for flexural strength using the three-point bending method. The sample size was 10×10×60 mm, the span was 20 mm, and the loading rate was 0.5 mm / min. The flexural strength calculation formula is as follows: R = 3PL / (2bh 2 ), where R represents the flexural strength (MPa); P represents the load on the sample when it breaks (N); L represents the span, i.e. the distance between the fulcrums (mm); b represents the width of the specimen (mm); and h represents the cross-sectional thickness of the specimen (mm).
[0035] The calcined samples of the embodiments and comparative examples were subjected to a thermal expansion instrument and the push rod method to measure the average thermal expansion coefficient of the samples at 25-800°C.
[0036] Example 1 Cordierite material prepared from magnesium waste porcelain
[0037] 1) Taking the magnesium waste porcelain and crushing it with a crusher, the D50 of the magnesium waste porcelain after crushing is 10-15 μm;
[0038] 2) 20wt% of magnesium waste porcelain, 26wt% of burned talc, 32wt% of kaolin and 22wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1220°C in an air atmosphere and kept warm for 30min to obtain a cordierite low-expansion heat-resistant material.
[0039] Example 2 Cordierite material prepared from magnesium waste porcelain
[0040] 1) Taking the magnesium waste porcelain and crushing it with a crusher, the D50 of the magnesium waste porcelain after crushing is 10-15 μm;
[0041] 2) 30wt% of magnesium waste porcelain, 20wt% of burned talc, 27wt% of kaolin and 23wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1220°C in an air atmosphere and kept warm for 30min to obtain a cordierite low-expansion heat-resistant material.
[0042] Example 3 Cordierite material prepared from magnesium waste porcelain
[0043] 1) Taking the magnesium waste porcelain and crushing it with a crusher, the D50 of the magnesium waste porcelain after crushing is 10-15 μm;
[0044] 2) 40wt% of magnesium waste porcelain, 14wt% of burned talc, 22wt% of kaolin and 24wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1220°C in an air atmosphere and kept warm for 30min to obtain a cordierite low-expansion heat-resistant material.
[0045] Example 4 Cordierite material prepared from magnesium waste porcelain
[0046] 1) Taking the magnesium waste porcelain and crushing it with a crusher, the D50 of the magnesium waste porcelain after crushing is 10-15 μm;
[0047] 2) 20wt% of magnesium waste porcelain, 26wt% of burned talc, 32wt% of kaolin and 22wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260℃ in an air atmosphere and kept warm for 30min to obtain a cordierite low-expansion heat-resistant material.
[0048] Example 5 Cordierite material prepared from magnesium waste porcelain
[0049] 1) Taking the magnesium waste porcelain and crushing it with a crusher, the D50 of the magnesium waste porcelain after crushing is 10-15 μm;
[0050] 2) 30wt% of magnesium waste porcelain, 20wt% of burned talc, 27wt% of kaolin and 23wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite low-expansion heat-resistant material.
[0051] Example 6 Cordierite material prepared from magnesium waste porcelain
[0052] 1) Taking the magnesium waste porcelain and crushing it with a crusher, the D50 of the magnesium waste porcelain after crushing is 10-15 μm;
[0053] 2) 40wt% of magnesium waste porcelain, 14wt% of burned talc, 22wt% of kaolin and 24wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the mixture is passed through a 250-mesh sieve (the residue on the sieve is less than 0.1%). The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite low-expansion heat-resistant material.
[0054] Comparative Example 1
[0055] 40wt% of calcined talc, 40wt% of kaolin and 20wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite material.
[0056] Comparative Example 2
[0057] 1) Take daily waste porcelain and crush it with a crusher. The D50 of the waste porcelain raw material after crushing is 10-15 μm;
[0058] 2) 30wt% of daily waste porcelain, 37wt% of burned talc, 10wt% of kaolin and 23wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite material.
[0059] Comparative Example 3
[0060] 1) Take the waste porcelain from bathroom and crush it with a crusher. The D50 of the waste porcelain raw material after crushing is 10-15 μm;
[0061] 2) 30wt% of sanitary waste porcelain, 37wt% of burned talc, 10wt% of kaolin and 23wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite material.
[0062] Comparative Example 4
[0063] 1) Using a crusher to coarsely crush the magnesium waste porcelain, the D50 of the waste porcelain raw material after crushing is 75-106 μm;
[0064] 2) 40wt% of magnesium waste porcelain, 14wt% of burned talc, 22wt% of kaolin and 24wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the mixture is passed through a 250-mesh sieve (the residue on the sieve is less than 0.1%). The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite material.
[0065] Comparative Example 5
[0066] 1) Take daily waste porcelain and magnesium waste porcelain respectively, and crush them by a crusher. The D50 of the waste porcelain raw materials after crushing is 10-15 μm;
[0067] 2) 10wt% of daily waste porcelain, 30wt% of magnesia waste porcelain, 14wt% of calcined talc, 22wt% of kaolin and 24wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite material.
[0068] Comparative Example 6
[0069] 1) Take sanitary waste porcelain and magnesium waste porcelain respectively, and crush them by a crusher. The D50 of the waste porcelain raw materials after crushing is 10-15 μm;
[0070] 2) 10wt% of sanitary waste porcelain, 30wt% of magnesia waste porcelain, 14wt% of burned talc, 22wt% of kaolin and 24wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite material.
[0071] Comparative Example 7
[0072] 1) Take daily waste porcelain, bathroom waste porcelain, and magnesium waste porcelain respectively, and crush them by a crusher. The D50 of the waste porcelain raw materials after crushing is 10-15 μm;
[0073] 2) 5wt% of daily waste porcelain, 5wt% of bathroom waste porcelain, 20wt% of magnesia waste porcelain, 14wt% of burned talc, 22wt% of kaolin and 24wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite material.
[0074] Comparative Example 8
[0075] 1) Take daily waste porcelain, bathroom waste porcelain, and magnesium waste porcelain respectively, and crush them by a crusher. The D50 of the waste porcelain raw materials after crushing is 10-15 μm;
[0076] 2) 5wt% of daily waste porcelain, 5wt% of bathroom waste porcelain, 30wt% of magnesia waste porcelain, 14wt% of burned talc, 22wt% of kaolin and 24wt% of bauxite are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite material.
[0077] Example 7 Cordierite material prepared from magnesium waste porcelain
[0078] 1) Taking the magnesium waste porcelain and crushing it with a crusher, the D50 of the magnesium waste porcelain after crushing is 10-15 μm;
[0079] 2) 30wt% of magnesium waste porcelain, 22wt% of burnt talc, 30wt% of black mud and 18wt% of alumina powder are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%. The green body is prepared by semi-dry pressing (molding pressure 10MPa), and the green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite low-expansion heat-resistant material.
[0080] Example 8 Cordierite material prepared from magnesium waste porcelain
[0081] 1) Taking the magnesium waste porcelain and crushing it with a crusher, the D50 of the magnesium waste porcelain after crushing is 10-15 μm;
[0082] 2) 30wt% of magnesium waste porcelain, 25wt% of burned talc, 25wt% of bentonite and 20wt% of alumina powder are mixed and wet-milled, the ratio of material: ball mill: water is 1:2:1, the ball mill speed is 400r / min, the ball milling time is 60min, and the slurry is passed through a 250-mesh sieve (the sieve residue is less than 0.1%) after ball milling. The slurry is dried and granulated to obtain a green powder with a moisture content of 6%, and a green body is prepared by semi-dry pressing (molding pressure 10MPa). The green body is calcined at 1260°C in an air atmosphere and kept warm for 30min to obtain a cordierite low-expansion heat-resistant material.
[0083] Performance testing and results
[0084] The test results of the above embodiments and comparative examples are shown in the following table.
[0085]
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A cordierite material prepared from magnesium waste porcelain, characterized in that: The preparation raw materials include: magnesium waste porcelain, talc, clay raw materials, and high-aluminum raw materials. The weight percentage of the magnesium waste porcelain is 20-40%. After the raw materials are mixed, the molar ratio of magnesium oxide: aluminum oxide: silicon oxide is 0.29: (0.30-0.31): (0.76-0.80).
2. The cordierite material prepared from magnesium waste porcelain according to claim 1, characterized in that: The talc is burnt talc, the clay raw material is one or more of kaolin, illite, bentonite and black mud, and the high-alumina raw material is one or more of alumina, aluminum hydroxide and bauxite.
3. The cordierite material prepared from magnesium waste porcelain according to claim 2, characterized in that: The main crystal phases of the magnesium waste porcelain raw material are protoenstatite and magnesium-rich silicate glass phase.
4. The cordierite material prepared from magnesium waste porcelain according to claim 3, characterized in that: The D50 of the waste porcelain raw material is 10-15 μm, and the talc, clay raw materials and high-aluminum raw materials are sieved through a 250-mesh screen before molding.
5. The cordierite material prepared from magnesia waste porcelain according to any one of claims 1 to 4, characterized in that: The mass ratio of the magnesium waste porcelain, talc, clay raw material and high-aluminum raw material is (20-40): (14-26): (22-32): (22-24).
6. A method for preparing cordierite material using magnesium waste porcelain, characterized in that: The method comprises the following steps: mixing raw materials, ball milling, screening, granulating, molding, and calcining to obtain cordierite material; the raw materials comprise magnesia waste porcelain, talc, clay raw materials, and high-alumina raw materials, the weight percentage of the magnesia waste porcelain is 20-40%, and after the raw materials are mixed, the molar ratio of magnesium oxide: aluminum oxide: silicon oxide is 0.29: (0.30-0.31): (0.76-0.80).
7. The method for preparing cordierite material using magnesium waste porcelain according to claim 6, characterized in that: The talc is burnt talc, the clay raw material is one or more of kaolin, illite, bentonite and black mud, and the high-alumina raw material is one or more of alumina, aluminum hydroxide and bauxite.
8. The method for preparing cordierite material using magnesium waste porcelain according to claim 7, characterized in that: The main crystal phases of the magnesium waste porcelain raw material are protoenstatite and magnesium-rich silicate glass phase.
9. The method for preparing cordierite material using magnesium waste porcelain according to claim 8, characterized in that: The D50 of the waste porcelain raw material is 10-15 μm, and the talc, clay raw materials and high-aluminum raw materials are sieved through a 250-mesh screen before molding.
10. The method for preparing cordierite material by using magnesium waste porcelain according to any one of claims 6 to 9, characterized in that: The mass ratio of the magnesium waste porcelain, talc, clay raw material and high-aluminum raw material is (20-40): (14-26): (22-32): (22-24).
Citation Information
Patent Citations
Magnesian ceramic blank, magnesian ceramic and preparation method thereof
CN102786298A
Formula and preparation method for preform body of magnesia porcelain
CN106396617A
Cordierite ceramic synthesized from ceramic whiteware waste, and preparation method thereof
CN106518146A
Environment-friendly binary formula antique green glaze and preparation method thereof
CN118619549A
Cordierite-based aggregate and cordierite-based ceramic
JP1999349375A
Cited By
Preparation method of low-expansion high-strength petalite-cordierite multiphase ceramic green body and product of low-expansion high-strength petalite-cordierite multiphase ceramic green body
CN122380800A
Preparation method of low-expansion high-strength epi-dioptase-cordierite composite ceramic body and product thereof
CN122380800B